Multiplane Holographic Imaging Using the Spatial Light Modulator - Zhongsheng Zhai; Qinyang Li; Xuan He; Qinghua Lv; Wei Feng; Zhen Zeng; Xuanze Wang (Photonics, 2023)
The optimization of imaging accuracy and speed is a crucial issue in the development of computer-generated holograms (CGH) for three-dimensional (3D) displays. This paper proposes an optimized iterative algorithm based on the angular spectrum method (ASM) to achieve high-quality holographic imaging across multiple planes. To effectively utilize spatial resources for multi-image reconstruction and mitigate the speckle noise caused by the overlapping of target images, constraint factors are introduced between different layers within the same region. The seeking rule of the constraint factor is also analyzed. By utilizing both constraint factors and variable factors, the presented method is able to calculate phase holograms for target figure imaging at four different planes. Simulation and experimental results demonstrate that the proposed method effectively improves the overall quality of the different planes, thus holding great potential for wide-ranging applications in the field of holography.